Successful Cooperation between the Ministry of Finance and Local Governments for Implementing Regional Financial Management: Key Factors - Marwanto Harjowiryono; Rudy Widodo; Aditya Agung Satrio; Teguh Dwi Prasetyo (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
This study aimed to evaluate the Ministry of Finance role in providing mentoring to Local Governments for the implementation of regional financial management. Financial advisor role is a strategic step to foster synergy and collaboration with Local Governments in the field of national financial management. A qualitative approach and an exploratory design were used followed by SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The analysis was used to provide recommendations for the Ministry of Finance and Local Governments to implement regional financial management strategies. Data collection methods varied for all subjects. Internal data from the Ministry of Finance were obtained through interviews and document studies, while external data were collected through the completion of questionnaires by 461 Local Governments and document studies. The results showed that Local Governments require coordination and mentoring from the Ministry of Finance regarding regional financial management. The Ministry of Home Affairs has the authority to guide Local Governments in terms of institutional structure. Moreover, the Ministry of Finance can voluntarily offer mentoring by demonstrating the positive aspects of work and illustrating the benefits of financial advisor role, as explained in the rational choice theory.